TUG1 promotes prostate cancer progression by acting as a ceRNA of miR-26a. Issue 5 (2nd October 2018) - Yang, Bin; Tang, Xiaodi; Wang, Zhixin; Sun, Daju; Wei, Xin; Ding, Youpeng
Abstract : Previous studies have demonstrated that taurine-upregulated gene 1 (TUG1) was aberrantly expressed and involved in multiple types of cancer; however, the expression profile and potential role of TUG1 in prostate cancer (PCa) remains unclear. The aim of the present study was to evaluate the expression and function of TUG1 in PCa. In the present study, we analyzed TUG1 expression levels of PCa patients in tumor and adjacent normal tissue by real-time quantitative PCR. Knockdown of TUG1 by RNAi was performed to explore its roles in cell proliferation, migration, and invasion. Here we report, for the first time, that TUG1 promotes tumor cell migration, invasion, and proliferation in PCa by working in key aspects of biological behaviors. TUG1 could negatively regulate the expression of miR-26a in PCa cells. The bioinformatics prediction revealed putative miR-26a-binding sites within TUG1 transcripts. In conclusion, our study suggests that long non-coding RNA (lncRNA) TUG1 acts as a functional oncogene in PCa development.